2009
DOI: 10.1160/th08-12-0810
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms enhance platelet-mediated thrombogenicity

Abstract: Although it is generally acknowledged that serotonin (5-HT) is a weak agonist for human platelets, recent information suggests an association between serotonergic mechanisms and cardiovascular risk. We investigated the action of 5-HT on adhesive, cohesive and procoagulant properties of human platelets. Impact of 5-HT on whole blood coagulation and thrombin generation was measured by modified thromboelastometry (TEM) and specific fluorogenic assays. We evaluated the effects of 5-HT on thrombus formation in an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…Platelet SERT density correlated closely with P-selectin expression, a marker of platelet activation and cell-cell interaction, consistent with the concept of 5HT as a weak agonist [265]. However, Galan et al concluded that, contrary to tradition, 5HT is not a weak agonist of platelets, but instead sensitizes them or potentiates their responsiveness [266]. …”
Section: Serotonin: a Platelet-neuron Nexus?supporting
confidence: 58%
See 1 more Smart Citation
“…Platelet SERT density correlated closely with P-selectin expression, a marker of platelet activation and cell-cell interaction, consistent with the concept of 5HT as a weak agonist [265]. However, Galan et al concluded that, contrary to tradition, 5HT is not a weak agonist of platelets, but instead sensitizes them or potentiates their responsiveness [266]. …”
Section: Serotonin: a Platelet-neuron Nexus?supporting
confidence: 58%
“…The relative potency may be misleading since it is based on data in vitro whereas in vivo several of these agonists, especially the "weak" ones, can act synergistically to potentiate or "prime" responses to others [5]. For example, serotonin [266,319]; and vWF-induced aggregation requires co-stimulation (including by ristocetin, an antibiotic used in laboratory studies) or conformation change of vWF. Information on the GPCR's is simplified from Ch.…”
Section: Platelet Basicsmentioning
confidence: 99%
“…Serotonin is essential to normal platelet function. A critical component of platelet activation is serotonin secretion, which has a number of different effects, including: 1) strong vasoactive properties through direct action on serotonin receptors and nitric oxide production, 2) the potentiation of the aggregation induced by adenosine diphosphate, epinephrine and collagen, and 3) the enhancement of fibrin formation (1215). …”
Section: Platelets and Serotoninmentioning
confidence: 99%
“…Serotonin is a weak platelet activator promoting hemostasis by enhancing platelet alpha granule release and by enhancing plasmatic coagulation [17], [18], [19], [20]. Together with ADP, serotonin is stored in platelet dense granules (at millimolar concentrations) and released upon platelet activation, locally reaching micromolar levels at sites of coronary atherothrombosis [21], [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Released serotonin is also a potent vasoconstrictor of coronary arteries with damaged endothelium [24]. Serotonin antagonism as well as platelet serotonin depletion by treatment with selective serotonin reuptake inhibitors have both been associated with a reduction in arterial thrombogenicity [17], [25], [26]. Therefore, serotonin antagonism in addition to established therapies might be a promising approach to improve the treatment of CAD patients.…”
Section: Introductionmentioning
confidence: 99%